Research-based planning for public libraries increasing relevance in the digital age - Matthews, Joseph R. (Santa Barbara, California Libraries Unlimited, an inprint of ABL-CIO, LLC, 2013)
"This book will help public library administrators, managers, and board members to better plan, strategize, and understand their communities, enabling public libraries to become dynamic, proactive institutions"-- Provided by publisher
Includes bibliographical references and index.
Keywords: Public libraries -- Planning; Public libraries -- Evaluation; Public libraries -- Collection development; Libraries -- Special collections -- Electronic information resources; Electronic information resources -- Management; Public libraries -- Aims and objectives; Libraries and community; Libraries and the Internet